How Do Firms Use Information Disclosure to Cope with Financing Constraints? Evidence from Earnings Management Using Classification Shifting (Journal of Global Humanities and Social Sciences, 2025)
This study empirically investigates the impact of financing constraints on earnings management using classification shifting (hereafter, classification shifting) based on a sample of A-share listed companies in China from 2003 to 2024. We find that, in order to alleviate financing constraints, management tends to engage more in classification shifting to smooth profits or enhance reported financial performance. Our study highlights that creditors and other stakeholders should pay close attention to firms' use of classification shifting as a means to cope with financing constraints.